The THE FEATURE OF SLEEP QUALITY IN CANCER PATIENTS UNDERGONE RADIOTHERAPY IN SANGLAH HOSPITAL DENPASAR - Gautama, Cindy (E-Jurnal Medika Udayana; Vol 10 No 7 (2021): Vol 10 No 07(2021): E-Jurnal Medika UdayanaDO - 10.24843/MU.2021.V10.i7.P01, 2021)
Background: Sleep disturbance is a complication that is often found in cancer patients, especially advanced-stage cancer. Cancer patients may experience sleep disturbances due to the direct effects of the neoplasm, the consequences of surgery, chemotherapy and/or radiotherapy, pain, delirium, opioids, or other psychological/psychiatric conditions. Cancer patients need quality sleep to maintain their optimal condition and immune system. Aim: Determine the sleep quality in cancer patients undergoing radiotherapy. Method: This research is a descriptive study with a cross-sectional design. The study population was cancer patients who underwent radiotherapy at Sanglah General Hospital in Denpasar during August 2020 - September 2020. The total sample obtained was 45 samples. The sample selection was done by consecutive sampling. The measuring instrument used in assessing sleep quality is the Pittsburgh Sleep Quality Index (PSQI). Result: The mean age in the sample of this study was 52 years old and 100% of samples were married. Most of the samples were female (74.6%). Based on the level of education, more samples have primary school education (46.7%). Most of the samples in this study did not work (40%). The finding of sleep quality in this study was more samples with poor sleep quality (84.4%) than those with good sleep quality (15.6%) based on the PSQI. Conclusion: The sleep quality of cancer patients undergoing radiotherapy at Sanglah General Hospital Denpasar is mostly poor, so it is necessary to carry out a holistic treatment starting from early detection to the management of poor sleep quality.